IDENTIFIKASI KARAKTERISTIK KREATIVITAS MASYARAKAT MENUJU DESA INOVATIF (Studi di Desa Kawasen Kecamatan Banjarsari Kabupaten Ciamis) - DINI YULIANI; KIKI ENDAH; ASEP NURWANDA (Universitas Galuh Ciamis, 2018)
The change of direction of development at the Village level forces the village government to more creatively seek opportunities and develop quality businesses based on the local wisdom of the community to improve the welfare of its people. Villagers are not people without knowledge and understanding, but individual knowledge of the village community is still a tacit knowledge or knowledge in the mind. So that the effort and the role of some parties, including from the academic circles so that their knowledge becomes knowledge that can be poured and practiced. The method used in this research is observation, literature study and documentation, and by conducting in-depth interviews to some village apparatus of Kawasen, head of RT and RW, community leaders and some people who have business activities that utilize the potential of Kawasen Village. The results of this study indicate that the efforts that have been done by the people of Kawasen Village have not given good results to the welfare of society in general. Kawasen village has various potential, such as wicker business from stick, opak business, banana chips business, there are also some people who develop organic rice farming based on the understanding passed down by the previous people. The units of economic activity already exist but community competence and marketing opportunities are still low. So that required training and coaching by the village government to provide motivation for people to be able to utilize existing technology around the environment, able to compete with people residing in other areas. Keywords: Identification, Innovative Village.